Bedside to Blueprints: The Role of Nurses in Hospital Design. (July 2014) - Clark, Erin
OBJECTIVE: To explore the role and function of nurses in the healthcare design industry. BACKGROUND: The design of a new hospital requires collaboration among multiple disciplines to develop an environment that allows for high-quality care to be delivered and received. This article investigates the role of nurses as an integral part of the design team when creating optimal spaces for patients and caregivers. While nurses fulfill many roles in healthcare, this investigation focused on the role of nurses as end-users, nurse leaders, and consultants. METHODS: An informal interview method was used to elicit information from 13 members of the healthcare design industry across disciplines and across the United States. Those interviewed included nurses, architects, and consultants. RESULTS: Common themes that emerged from this investigation included the importance of nurses as an integral part of the design team and a continued need to understand optimal utilization to be an effective team member. A number of organizations and events welcome nurses to help foster design innovation and interprofessional collaboration. CONCLUSIONS: The role of the professional nurse continues to expand and there are many opportunities for nurses to step out of their traditional role and into the industry of healthcare design.